Exploring the potential health benefits from Hermetia illucens and Chrysomya chloropyga larvae meal in poultry diets - Van Emmenes, Liesel (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDAgric)--Stellenbosch University, 2021.